THE EFFECT OF LEARNING STRATEGY AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES MADRASAH IBTIDAIYAH STATE 3 ACEH SOUTH - Fitri Wahyuni (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out: (1) the effect of the application of learningstrategies on students' Fikih learning outcomes, (2) the effect of learningmotivation on student Fikih learning outcomes, and (3) the interactionbetween learning strategies and learning motivation towards Fikihlearning outcomes. The population of this study was all students in class VMIN 3 Aceh Tenggara consisting of 3 classes. Based on Cluster Random sampling techniques, one class as a collaborative learning class and one competitive learning class. The research instrument is a test used to obtainlearning outcome data and questionnaires to obtain data on studentlearning motivation. The normality test of the learning outcome data is theLiliefors test and the homogeneity test is the Fisher test and the Bartletttest. The analysis technique is two-way Anova at significance  = 0.05followed by the Scheffe test. The results showed: (1) the average learningoutcomes of students taught with collaborative learning strategies X =28.15 higher than the average learning outcomes of students taught withcompetitive learning strategies X = 26.92, with Fcount = 29.57 > Ftable =3.968, (2) the average learning outcomes of students with high learningmotivation X = 29.93 higher than the learning outcomes of students withlow learning motivation X = 25.94 with Fcount = 4.43 > Ftable = 3.968, and (3)there is an interaction between learning strategies and learning motivationtowards Fikih learning outcomes with Fcount = 7.18 > Ftable = 3.968.